Optimization of Rhodamine B Decolorization by Adsorption and Photoelectrodegradation Combination System - Sayekti Wahyuningsih; Velina Anjani; Hanik Munawaroh; Candra Purnawan (ALCHEMY Jurnal Penelitian Kimia, 2018)
A combination of adsorption and photoelectrodegradation system was performed to reduce the concentration of Rhodamine B dye in water. The adsorption was conducted using silica and alumina activated by acid and base under various predetermined pH of Rhodamine B. The photoelectrodegradation process was performed using Ti/TiO2 electrode as a cathode and Ti/TiO2-NiO as an anode. TiO2 was synthesized from titanium tetra-isopropoxide precursor (TTiP) by sol-gel method. TiO2-NiO composite was synthesized with the same precursor with the addition of Ni(NO3)2.6H2O. The result shows that the activation changes the amount of OH total in the adsorbent. The acid-activated adsorbent showed an optimum adsorption activity when Rhodamine B was in base condition caused by zwitter ionic structure. It reversely occured to base-activated adsorbent where an optimum absorption activity reached at acid condition. The application of base-activated silica in adsorption and photoelectrodegradation combination system decreased the concentration of Rhodamine B dye up to 98.79% using photoanode Ti/TiO2-NiO under pH 2 at bias potential 6 V.